2016
DOI: 10.1016/j.mri.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Imaging signatures of meningioma and low-grade glioma: a diffusion tensor, magnetization transfer and quantitative longitudinal relaxation time MRI study

Abstract: Differentiation of cerebral tumor pathology currently relies on interpretation of conventional structural MRI and in some cases histology. However, more advanced MRI methods may provide further insight into the organization of cerebral tumors and have the potential to aid diagnosis. The objective of this study was to use multimodal quantitative MRI to measure the imaging signatures of meningioma and low-grade glioma (LGG). Nine adults with meningioma and 11 with LGG were identified, and underwent standard stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…However, no sets of phenotypic features have been consistently demonstrated to significantly associate with meningioma grade across studies. Differences between meningioma and low grade glioma was investigated using imaging features from T1-weighed and DWI[ 53 ], however, the study presented several limitations including a small sample size (n = 15). Some studies investigating imaging features suggest that benign tumors display higher ADC while malignant tumors have lower ADC values[ 54 56 ], while others fail to corroborate a similar relationship [ 57 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, no sets of phenotypic features have been consistently demonstrated to significantly associate with meningioma grade across studies. Differences between meningioma and low grade glioma was investigated using imaging features from T1-weighed and DWI[ 53 ], however, the study presented several limitations including a small sample size (n = 15). Some studies investigating imaging features suggest that benign tumors display higher ADC while malignant tumors have lower ADC values[ 54 56 ], while others fail to corroborate a similar relationship [ 57 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…They reported that it provided additional information for a definitive diagnosis. Piper et al 32 reported that multimodel MRI parameters (AD, RD, FA, and quantitative longitudinal relaxation time and magnetization transfer ratio) could be useful in differentiating between low-grade glioma and meningioma. To the best of our knowledge, this is the first study reporting that a combined use of all MR DTI parameters (ADCmin, ADCmean, ADCmax, FA, AD, RD, rADCmin, rADCmax, rADCmean, rFA, rAD, and rRD) provides higher diagnostic accuracy for the differentiation of low-from high-grade meningioma.…”
Section: Discussionmentioning
confidence: 99%
“…The inability to analyse high and low grade correctly lies at the basis of misdiagnosis of glioma grades [20]. Using T1-weighted and diffusionweighted imaging features, the meningioma and LGG were examined in a small sample set, but the small dataset limited the results [17]. Various radiomics features can be extracted from 2D or 3D tumour images depending on their size and shape.…”
Section: Discussionmentioning
confidence: 99%